Pembuatan Aplikasi Mobile Tourism Guide Kota Malang dan Kota Batu Berbasis Android - Hartanto, Kelvin; Andjarwirawan, Justinus; Setiawan, Alexander (Jurnal Infra, 2015)
Indonesia has a lot of cities, each of which has many tourism atrraction. One of the two cities are famous for tourism place, the city of Malang and Batu. Both of these cities the distance very close to one another. Both the city is also famous for the cool air, and culinary. Many of the tourists who vacation in the city, but tourists and residents around the city are still many who do not know the tourism place that are in both cities. It therefore requires a source of information that is easy to understand and easy to obtain. With the use of smartphones are widely used today, then designed an application to provide information about the tourism place in the city of Malang and Batu.This application provides a variety of information, especially the tourism place, culinary, and hotels in the city of Malang and Batu. Information about the culinary, hotel, and tourism are categorized by the administrator, accompanied by photographs and a detailed description with the goal of keeping the tourists and residents can understand clearly. This application also has many features such as nearby, get route, GPS, maps, tourism tour, review, and rating. The application is designed to operate on smartphones with Android operating system.From the test results, the application can perform the function of maps, get the route, nearby as well as other functions such as ratings, and reviews. So that a user who will be traveling to the city of Malang and Batu can use the features of this application.